STRATEGI GURU PAI DALAM PEMANFAATAN MEDIA PEMBELAJARAN UNTUK MENINGKATKAN PEMAHAMAN ASMAUL HUSNA SISWA SEKOLAH DASAR - Jannah, Makhfirah Jannatun; Nurmayani, Nurmayani; Nadhilah Syafitri; Dea Febria Br Ketare; Dwi Anggina Pasha Dalimunthe; Azzahra Julaika (Universitas Negeri Medan, 2025)
This study aims to analyze the use of learning media by Islamic Religious Education (PAI) teachers to improve students’ understanding of Asmaul Husna in elementary schools. The research employed a qualitative approach with a case study design. Data were collected through semi-structured interviews, observation, and documentation. The findings indicate that teachers implemented a gradual memorization strategy, introducing five names of Allah each semester to match students’ cognitive abilities. Songs were found to be the most effective medium, as they not only facilitated memorization but also helped students comprehend the meaning. In addition, teachers used simple technology such as laptops and smartphones to play songs and videos, as well as supplementary media like flashcards, posters, and worksheets. Technological limitations were overcome through collaboration between teachers and students. Overall, the study concludes that integrating traditional and modern media creates an engaging learning atmosphere, enhances comprehension, and fosters religious values in students from an early age.